2022
DOI: 10.1007/s11307-022-01723-3
|View full text |Cite
|
Sign up to set email alerts
|

Immune Activation in Pregnant Rats Affects Brain Glucose Consumption, Anxiety-like Behaviour and Recognition Memory in their Male Offspring

Abstract: Purpose Prenatal infection during pregnancy is a risk factor for schizophrenia, as well as for other developmental psychiatric disorders, such as autism and bipolar disorder. Schizophrenia patients were reported to have altered brain metabolism and neuroinflammation. However, the link between prenatal infection, altered brain inflammation and metabolism, and schizophrenia remains unclear. In this project, we aimed to evaluate whether there are changes in brain glucose consumption and microglia ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 69 publications
(78 reference statements)
1
3
0
Order By: Relevance
“…Our results showed a significant effect of the PND factor in global brain metabolism, with higher values in PND100 vs. PND35, regardless of phenotype. These results are similar to that found by Guerrin et al ( 2022 ), showing a progressive increase of brain metabolism with age in the frontal cortex in MIS male offspring. Besides, voxel-wise results showed increased FDG uptake in the cerebellum of MIS adolescent females compared to Saline animals, but this modulation was not present in adulthood.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results showed a significant effect of the PND factor in global brain metabolism, with higher values in PND100 vs. PND35, regardless of phenotype. These results are similar to that found by Guerrin et al ( 2022 ), showing a progressive increase of brain metabolism with age in the frontal cortex in MIS male offspring. Besides, voxel-wise results showed increased FDG uptake in the cerebellum of MIS adolescent females compared to Saline animals, but this modulation was not present in adulthood.…”
Section: Discussionsupporting
confidence: 92%
“…The cerebellar metabolic changes that we observed are relatively controversial. On the one hand, they mimic the hypermetabolism shown in males at PND21, which is not present in older ages (Guerrin et al, 2022) but highly contrast with the metabolic reduction found in males of the same age (i.e., PND35; Hadar et al, 2015). Therefore, the temporal nature of this metabolic feature could be indicative of the delayed neurodevelopmental impairment in females, implying a delay in achieving the same cerebellar metabolic reduction as observed in males.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Even though the research results may differ across the specific Poly (I: C) schemes in different studies, the aberrant cognitive behaviors of offspring seemed to be manifested at a certain stage of growth (44,45). Thus, the existence of the behaviors related to cognitive dysfunction helped to confirm harmful factors from the previous maternal Poly (I: C) exposure that caused perturbed neurodevelopment in offspring.…”
Section: Discussionmentioning
confidence: 98%